1997
DOI: 10.1038/ng1297-404
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin is required for neurogenesis and is not impaired by the Huntington's disease CAG expansion

Abstract: Huntington's disease (HD) is an autosomal-dominant neurodegenerative disorder caused by a CAG repeat expansion that lengthens a glutamine segment in the novel huntingtin protein. To elucidate the molecular basis of HD, we extended the polyglutamine tract of the mouse homologue, Hdh, by targetted introduction of an expanded human HD CAG repeat, creating mutant HdhneoQ50 and HdhQ50 alleles that express reduced and wild-type levels of altered huntingtin, respectively. Mice homozygous for reduced levels displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
328
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(348 citation statements)
references
References 42 publications
14
328
0
4
Order By: Relevance
“…Previous work demonstrated that homozygous mice with a targeted disruption in the Htt gene do not survive to term and suffer early postimplantation embryonic lethality (Duyao et al, 1995;Nasir et al, 1995;Zeitlin et al, 1995;White et al, 1997). More recent morphometric and ultrastructural analysis performed on heterozygous mice, which survive to adulthood, identified neuronal loss with signs of apoptosis in the basal ganglia of adult animals (O'Kusky et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work demonstrated that homozygous mice with a targeted disruption in the Htt gene do not survive to term and suffer early postimplantation embryonic lethality (Duyao et al, 1995;Nasir et al, 1995;Zeitlin et al, 1995;White et al, 1997). More recent morphometric and ultrastructural analysis performed on heterozygous mice, which survive to adulthood, identified neuronal loss with signs of apoptosis in the basal ganglia of adult animals (O'Kusky et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Mice with a targeted disruption of the Htt gene die at embryonic day 7.5 (Duyao et al, 1995;Nasir et al, 1995;Zeitlin et al, 1995). Moreover, analysis of mice expressing Ͻ50% of wtHtt showed extensive brain abnormalities and died shortly after birth (White et al, 1997). These data suggest that Htt is an important factor during embryonic development and that its role is not restricted to the nervous system.…”
mentioning
confidence: 89%
“…Two interesting peculiarities arose from previous investigations, that could explain the pathogenic phenomenon of expanded polyglutamines: their increasing ability to form amyloid-like protein aggregates with the elongation of the polyQ stretches [10,14,15], and the specific capability to be recognized by the 1C2 and 1F8 MoAbs [20,21], Abs whose affinity increases with the elongation of the polyQ stretches.…”
Section: Introductionmentioning
confidence: 99%
“…Hdh knock-in Mice. White et al (1997) developed a mouse model of Huntington's disease by extending the polyglutamine tract of the murine homolog (Hdh) of the human huntingtin gene (HD). CAG repeats from an HD chromosome were inserted into the appropriate position in Hdh exon 1, altering the mouse HD homolog to encode huntingtin protein with 50, 92, or 111 glutamine residues, instead of the 7 normally found in the mouse protein.…”
Section: Transgenic Mice Expressing Full-length Human Mutant Huntingtinmentioning
confidence: 99%